The Influence Of Health Education Using Animated Video Media On The Level Of HIV/AIDS Knowledge In Adolescent Women At SMA N 1 Mlati Sleman Yogyakarta - Ravicka Rahmawati; Nur Rahmawati Sholihah (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: In Indonesia, HIV/AIDS cases increase every year. HIV cases reached their peak in 2019, with 50,282 cases and an incidence of 8 people per 100,000 population. Globally, the vulnerable generation of young people aged 10- 19 years have 75% knowledge about HIV/AIDS. Adolescent behavior towards preventing HIV/AIDS is currently still not optimal, namely 30-45%. Meanwhile, only 10% have 100% accurate knowledge, therefore to reduce the incidence of HIV/AIDS among teenagers, efforts are needed to increase knowledge about HIV/AIDS among teenagers. Objective: The aim of this research is to determine the effect of health education using animated video media on the level of HIV/AIDS knowledge among young women at SMA N 1 Mlati Sleman Yogyakarta. Research Method: This research uses quantitative research with a pre-experiment one group pretest-posttest research design. The sample in the research was 72 young women at SMA N 1 Sleman. Data was obtained using a questionnaire and analyzed using the mann whitney. Results: The results of data analysis obtained a p-value = 0.000 (<0.05) so it can be concluded that there is an influence of health education with animated videos on the level of HIV/AIDS knowledge among young women at SMA N 1 Mlati Sleman Yogyakarta. Conclusion: The conclusion is that there is an influence of health education with animated videos on the level of HIV/AIDS knowledge among young women at SMA N 1 Mlati Sleman Yogyakarta.